Evaluation of 2G and 4G Cellular Network Performance Along the Trans Padang–Bungus Route - Tri Sukma Afani; Muhammad Putra Pamungkas; Yulindon (Politeknik Negeri Padang, 2026)
The quality of mobile telecommunication services is a vital parameter in supporting the connectivity of public transport passengers, particularly on routes with significant topographical challenges. This study aims to evaluate the performance of 2G and 4G LTE networks along the Transpadang Bungus Corridor route in Padang City to map signal quality and identify areas with low performance. The research materials involve the use of hardware in the form of smartphones integrated with TEMS Pocket software for field data collection, as well as TEMS Discovery for statistical data processing and geographical visualization. The method employed is a continuous drive test along the route to collect technical parameters in real-time. Measurement results indicate that on the 2G network, the RxLev parameter is dominated by the